The Catholic Church and social work : types of Catholic Welfare Agencies in the Vicariate of Cape Town - Perquin, A. N (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- Universiteit van Stellenbosch, 1940.